Didymella acutilobae sp. nov. Causing Leaf Spot and Stem Rot in Angelica acutiloba - Gyo-Bin Lee; Ki Deok Kim; Weon-Dae Cho; Wan-Gyu Kim (Mycobiology)
During disease surveys of Angelica acutiloba plants in Korea, leaf spot symptoms were observed in a field in Andong in July 2019, and stem rot symptoms in vinyl greenhouses in Yangpyeong in April 2020. Incidence of leaf spot and stem rot of the plants ranged from 10 to 20% and 5 to 30%, respectively. Morphological and cultural characteristics of fungal isolates from the leaf spot and stem rot symptoms fitted into those of the genus Phoma. Molecular phylogenetic analyses of two single-spore isolates from the symptoms using concatenated sequences of LSU, ITS, TUB2, and RPB2 genes authenticated an independent cluster from other Didymella (anamorph: Phoma) species. Moreover, the isolates showed different morphological and cultural characteristics in comparison to closely related Didymella species. These discoveries confirmed the novelty of the isolates. Pathogenicity of the novel Didymella species isolates was substantiated on leaves and stems of A. acutiloba through artificial inoculation. Thus, this study reveals that Didymella acutilobae sp. nov. causes leaf spot and stem rot in Angelica acutiloba.